2014
DOI: 10.1371/journal.pone.0099195
|View full text |Cite
|
Sign up to set email alerts
|

β-Adrenergic Receptor-Dependent Alterations in Murine Cardiac Transcript Expression Are Differentially Regulated by Gefitinib In Vivo

Abstract: β-adrenergic receptor (βAR)-mediated transactivation of epidermal growth factor receptor (EGFR) has been shown to promote cardioprotection in a mouse model of heart failure and we recently showed that this mechanism leads to enhanced cell survival in part via regulation of apoptotic transcript expression in isolated primary rat neonatal cardiomyocytes. Thus, we hypothesized that this process could regulate cardiac transcript expression in vivo. To comprehensively assess cardiac transcript alterations in respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…This calculation estimated the change of expression levels at the start of cultivation (intercept), and the temporal trend during 35 days of culture (slope×35). Genes were selected that represent cardiomyocyte characteristics, or the pathology of myocardial disease, such as (1) heart failure 40 , (2) cardiac hypertrophy 41,42 , and (3) β-adrenergic stimulation 43,44 . Complete mRNA expression data are provided as Supplementary Data 1…”
Section: Resultsmentioning
confidence: 99%
“…This calculation estimated the change of expression levels at the start of cultivation (intercept), and the temporal trend during 35 days of culture (slope×35). Genes were selected that represent cardiomyocyte characteristics, or the pathology of myocardial disease, such as (1) heart failure 40 , (2) cardiac hypertrophy 41,42 , and (3) β-adrenergic stimulation 43,44 . Complete mRNA expression data are provided as Supplementary Data 1…”
Section: Resultsmentioning
confidence: 99%
“…ISO, an adrenergic agonist, is a widely used for studying cardiac pathobiology in experimental animals (Seifert, 2013). However, studies on its effects on gene expression in the heart have largely been restricted to a handful of genes of interest and fewer analyses of the total transcriptome from ISO treated heart have been reported till date (Li et al, 2003;Lu et al, 2012;Talarico et al, 2014). To establish the efficacy of TA in ameliorating CH, we undertook the total transcriptomic analyses of ISO/TA treated rat heart.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that the ISO treated heart needs to reset its function through the readjustment of its genome wide expression profile. To be noted that Talarico et al (2014) have reported change in expression of 493 genes in mouse heart following ISO treatment for an hour. Considering the species difference and experimental parameters like the dose and duration of treatment, our data is largely in tune with theirs ( Supplementary Table S4).…”
Section: Discussionmentioning
confidence: 99%
“…β2-AR stimulation also increases the expression of the soluble inhibitory binding protein of IL-18, limiting pathological hypertrophy of the myocardium [116]. In other contexts, isoproterenol stimulation of β-AR promotes transactivation of epidermal growth factor receptor (EGFR), which signals to inhibit transcription of pro-inflammatory cytokines and pro-apoptotic factors in CMs [117][118][119]. Opioid receptor agonists such as morphine also facilitate cardioprotection through the delta-opioid receptor, increasing transcription of sarcomeric stress response proteins, repressing inflammation, and expressing miR-133b-5p to inhibit CM apoptosis [120][121][122][123].…”
Section: Gpcr-stimulated Pathways Of Gene Expressionmentioning
confidence: 99%